Ultrastructure of cerebral arteries following experimental subarachnoid haemorrhage. Issue 3 (March 1985) - Pickard, J D; Graham, D I; Matear, E; MacPherson, P; Tamura, A; Fitch, W
Abstract : Scanning and transmission electron microscopy have been used to examine the ultrastructure of cerebral arteries taken from dogs up to nine days following the injection of autologous blood into the suprachiasmatic cistern and using meticulous perfusion-fixation technique. No ultrastructural changes in the cerebral arteries were noted either at sites of radiologically demonstrated arterial constriction or elsewhere. The only abnormality noted was the presence of some leucocytes and macrophages in the subarachnoid space surrounding the arteries. These results are discussed in relation to changes in cerebrovascular reactivity that occur at this stage following subarachnoid haemorrhage.